"Our nurse is the glue for our team" - Multidisciplinary team members' experiences and perceptions of the gynaecological oncology specialist nurse role. (August 2019) - Cook, Olivia; McIntyre, Meredith; Recoche, Katrina; Lee, Susan
Abstract: Purpose: To determine how members of gynaecological oncology multidisciplinary teams experience and perceive the specialist nurse role. Methods: Members of gynaecological oncology multidisciplinary teams were recruited via two professional organisations to participate in an online qualitative survey. Survey responses were subjected to an inductive content analysis and categorised according to meaning. Results: Sixty-six (n = 66) multidisciplinary team members participated in the online survey. Most participants worked in metropolitan areas and within the public health care system. 71% (n = 47) of participants had a specialist nurse working in their team. Participants without a specialist nurse in their team (n = 19) believed that this was a disadvantage to the women in their care except where other experienced nurses were able to fill this void. Key aspects of the specialist nurse role identified by multidisciplinary team members included: Contact, communication, and coordination; Support and advocacy; Knowledge and education; Assessment, referral and management. Concerns and disadvantages relating to the role identified by team members included the development of dependence on the specialist nurse, the impact of large workloads, and the oversight of what other nurses can offer the patients. Conclusions: This study has contributed the perspective of a key stakeholder, the multidisciplinary team, to our understanding of the gynaecological oncology specialist nurse role. Clearer definition of specialist nurse roles is required. Standardised nomenclature and guidelines for practice are recommended to ensure that the specialist nurse role and their scope of practice are clear to key stakeholders and over-dependence on the individual in the role is mitigated. Highlights: Multidisciplinary teams were largely supportive of the specialist nurse role in the provision of gynaecological cancer care. Key role aspects identified by multidisciplinary team members:education, communication, assessment, referral and advocacy. Teams without a specialist nurse saw this as a disadvantage except where other skilled nurses filled the void. Concerns were raised regarding dependence on the specialist nurse, large workloads, and oversight of other nurses skills.